2020
DOI: 10.3390/su12083494
|View full text |Cite
|
Sign up to set email alerts
|

The Challenge of Sustainable Development Goal Reporting: The First Evidence from Italian Listed Companies

Abstract: This research investigates the extent to which the voluntary disclosure of Sustainable Development Goals (SDGs), assumed to be the most recent innovation in social disclosures and corporate sustainability reporting, is diffused among Italian listed companies through different instruments of disclosure (voluntary or non-voluntary). Our findings reveal that SDGs awareness amongst the business community is high and that the majority of highly-traded, liquid, and highly-capitalized Italian companies have introduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
168
3
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(194 citation statements)
references
References 73 publications
19
168
3
4
Order By: Relevance
“…Sustainability reporting can influence corporate actions and consequently induce the implementation of the SDGs into business strategy [50] and be a significant driver of an organization's sustainability strategy [51]. However, previous research found that few companies had cited the SDGs in their reports [52,59]. Additionally, SDG reporting practices have been criticized for "rainbow washing", meaning that companies overuse SDG rainbow wheels focusing on style instead of content [59].…”
Section: Sustainable Development Goalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sustainability reporting can influence corporate actions and consequently induce the implementation of the SDGs into business strategy [50] and be a significant driver of an organization's sustainability strategy [51]. However, previous research found that few companies had cited the SDGs in their reports [52,59]. Additionally, SDG reporting practices have been criticized for "rainbow washing", meaning that companies overuse SDG rainbow wheels focusing on style instead of content [59].…”
Section: Sustainable Development Goalsmentioning
confidence: 99%
“…However, previous research found that few companies had cited the SDGs in their reports [52,59]. Additionally, SDG reporting practices have been criticized for "rainbow washing", meaning that companies overuse SDG rainbow wheels focusing on style instead of content [59]. Additionally, some authors emphasized that the reports do not explain how these Goals relate to one another or identify the drivers of the impacts [53,54].…”
Section: Sustainable Development Goalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparative studies, aimed at identifying the priority SDGs in the different industrial sectors, geographical areas, and different categories of subjects called upon to support the achievement of the SDGs (private sector, public sector, academic community, etc. [47,48]. 4.…”
mentioning
confidence: 99%
“…In the academic field, scientific research on the subject is still scarce. In fact, there are hardly any studies that analyze how the SDGs contribute to the creation of business value [9] or how the achievement of the SDGs is being supported by the private sector [5,10]. This is why a detailed analysis on how the private sector is contributing to sustainable development is needed.…”
Section: Introductionmentioning
confidence: 99%